The importance of recognizing the International Treaty in the CBD’s Protocol on access and benefit-sharing - CGIAR Systemwide Genetic Resources Programme (2010)
Since 2004, Bioversity International, through the CGIAR’s System-wide Genetic Resources Programme (SGRP), has contributed to the ongoing negotiations of a protocol on access and benefit-sharing under the Convention on Biological Diversity (CBD). This policy brief highlights the importance of the protocol reflecting countries’ interdependence on genetic resources for food and agriculture (GRFA) and clearly recognizing the multilateral system of access and benefit-sharing under the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGFA).